Aggregation of phosphate and 1‐tetradecyl‐3‐methylimidazolium chloride background electrolytes during micellar electrokinetic chromatography. Issue 7 (20th March 2015) - Kazarjan, Jana; Vaher, Merike; Kaljurand, Mihkel
Abstract : We report the possible aggregation of phosphate and ionic liquid (1‐tetradecyl‐3‐methylimidazolium chloride) based BGEs during MEKC. After a certain transit period, the aggregates appear as a random sequence of spikes on a UV detector signal. Root mean square values of the spikes and aggregation time ( T a ) were plotted against BGE concentrations. The observation suggests that MEKC is a simple and easy technique for micelle aggregation studies.